Incompatibilidade escolaridade-ocupação no Brasil : incidência de sobre-educação de mão de obra ou escassez de empregos qualificados? - Silva, Filipe Alrelio Gomes da (2022)
The Brazilian labor market has undergone significant changes in recent decades, including the increase in workers with higher education. However, there is an imbalance caused by over-education, causing inefficiency, a drop in productivity due to low wages and dissatisfaction with non-compatible jobs. The aim of this dissertation is to explain whether, in Brazil, over-education is caused by labor supply or job demand factors. For this, based on a panel of data from the Annual Report of Social Information (RAIS), for the period 2010-2019, micro and macroeconomic variables were analyzed, in addition to estimating the random effect model and robust standard errors of Newey-West. The results found indicate that over-education is caused both by the increase in workers with higher education and by the decrease or low growth in the demand for qualified jobs. Economic factors such as specialization of professions and increase in employment in the industrial sector also have a positive impact on over-education. Finally, it is concluded that the country must adopt public policies aiming not only to raise the level of qualification of workers, but also to improve the quality of education and create favorable economic conditions so that the growth in demand for qualified jobs is directly correlated to that of the supply of skilled workers and, thus, the market achieves a better result in the allocation of workers.